Mucocutaneous Leishmaniasis with Rare Manifestation in the Nasal Mucosa and Cartilage Bone Septal - Casalle, Nicole [UNESP]; Pinto Grifoni, Lais de Barros [UNESP]; Bosco Mendes, Ana Carolina [UNESP]; Delort, Sergio [UNESP]; Sgavioli Massucato, Elaine Maria [UNESP] (Hindawi Ltd, 2020)
Backgroud. Leishmaniasis is an infectious disease caused by protozoan of the genusLeishmaniathat can affect mucosal or cutaneous surfaces. It can manifest via buccal mucosa, associated with a skin lesion or as a secondary effect. Over the last 20 years, the number of cases of this disease is progressively increasing in Brazil. Therefore, the knowledge of this disease by health professionals is important in order to achieve a correct and early diagnosis, manly to prevent the deformities it may cause to the face.Case presentation. The aim of the present study was to report a case of mucocutaneous leishmaniasis with lesions on the palatine and pharyngeal mucosa in a patient with a previous report of rare lesions in the nasal mucosa and cartilage bone septal.Conclusions. We believe that the disclosure of such cases may be important for the correct and early diagnosis of these secondary injuries that may affect the oral mucosa.